2010
DOI: 10.1111/j.1399-3046.2010.01304.x
|View full text |Cite
|
Sign up to set email alerts
|

Liver retransplantation in children: The Atlanta experience

Abstract: Liver retransplantation is routinely offered at our institution. Previous reports document that patient and graft survival is significantly less after pediatric rLT compared to primary LT. This has engendered intense debate regarding optimal allocation of organs. Here, we examine our program's approach to pediatric hepatic retransplantation related to patient factors affecting outcomes. Between 1997 and 2009, 272 LTs were performed in 234 patients (mean survival 1994 +/- 1367 days) at our center. Thirty-four p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 20 publications
1
26
1
Order By: Relevance
“…Literature reports concerning pediatric re-LTX indicate a clear reduction of graft and patient survival after re-LTX in comparison with primary LTX (4,5,7,12,14,15). However, in contrast, two recent small single-center studies showed similar outcomes after primary LTX and re-LTX (6,16). There are also differing results concerning the impact of the re-transplantation time point.…”
Section: Discussionmentioning
confidence: 98%
“…Literature reports concerning pediatric re-LTX indicate a clear reduction of graft and patient survival after re-LTX in comparison with primary LTX (4,5,7,12,14,15). However, in contrast, two recent small single-center studies showed similar outcomes after primary LTX and re-LTX (6,16). There are also differing results concerning the impact of the re-transplantation time point.…”
Section: Discussionmentioning
confidence: 98%
“…Several previous studies of retransplantation conducted in single centers as well as using UNOS and SPLIT databases have reported protective and risk factors . A multivariate analysis of the UNOS database described number of retransplants, race, hospitalization in the ICU, weight, creatinine levels, bilirubin levels, donor age, and cold ischemia time as risk factors in retransplantation .…”
mentioning
confidence: 99%
“…A study using SPLIT retransplantation data found associations between survival at two yrs and donor age, use of a technical variant allograft, and INR at retransplant . Single‐center studies have also reported associations between survival and patient age, presence of cholestasis, congenital abnormalities, pretransplant ALT, donor age, donor cardiac death, regional vs. national allocation, and percent blood transfusion during transplant . A prognostic scoring tool constructed by Davis et al includes life support at retransplant, split liver graft, cholestasis or paucity of bile ducts, and congenital abnormalities as risk factors and older patient age and an indication of acute rejection as protective factors for retransplant patients.…”
mentioning
confidence: 99%
“…Although over time there has been a trend toward better survival in patients undergoing eRe‐LT, results are still significantly worse than after a first transplantation . Also, results in patients undergoing eRe‐LT are consistently worse than in those who undergo late re‐LT, and prognosis in the eRe‐LT patients is also worse than in those with the other classical indication for urgent LT: acute liver failure …”
Section: Discussionmentioning
confidence: 99%
“…(6)(7)(8)(9)(10)13,(16)(17)(18) Although over time there has been a trend toward better survival in patients undergoing eRe-LT, results are still significantly worse than after a first transplantation. (1,5,7,16,17,19,20) Also, results in patients undergoing eRe-LT are consistently worse than in those who undergo late re-LT, and prognosis in the eRe-LT patients is also worse than in those with the other classical indication for urgent LT: acute liver failure. (17) In a large single-center series of children undergoing LT, Venick et al found that eRe-LT was an independent prognostic factor for poor outcome.…”
Section: Original Article | 533mentioning
confidence: 99%